Design optimization of a short-term duty electrical machine for extreme environment - Arumugam, Puvaneswaran; Amankwah, Emmanuel K.; Walker, Adam; Gerada, C. (Institute of Electrical and Electronics Engineers, 2017)
This paper presents design optimisation of a short term duty electrical machine for extreme environments of high temperature and high altitudes. For such extreme environmental conditions of above 80⁰C and altitudes of 30km, thermal loading limits are a critical consideration in machines, especially if high power density and high efficiency are to be achieved. The influence of different material on the performance of such machines is investigated. Also the effect of different slot and pole combinations are studied for machines used for such extreme operating conditions but with short duty. In the research, A Non-dominated Sorting Genetic Algorithm (NSGAII) considering an analytical electromagnetic model, structural and thermal model together with Finite Element (FE) methods are used to optimise the design of the machine for such environments achieving high efficiencies and high power density with relatively minimal computational time. The adopted thermal model is then validated through experiments and then implemented within the Genetic Algorithm (GA). It is shown that, generally, the designs are thermally limited where the pole numbers are limited by volt-amps drawn from the converter. The design consisting of a high slot number allows for improving the current loading and thus, significant weight reduction can be achieved.